Abnormal P‐wave terminal force in lead V1 is a marker for atrial electrical dysfunction but not structural remodelling. (30th June 2021) - Lebek, Simon; Wester, Michael; Pec, Jan; Poschenrieder, Florian; Tafelmeier, Maria; Fisser, Christoph; Provaznik, Zdenek; Schopka, Simon; Debl, Kurt; Schmid, Christof; Buchner, Stefan; Maier, Lars S.; et al.
Abstract: Aims: There is a lack of diagnostic and therapeutic options for patients with atrial cardiomyopathy and paroxysmal atrial fibrillation. Interestingly, an abnormal P‐wave terminal force in electrocardiogram lead V1 (PTFV1 ) has been associated with atrial cardiomyopathy, but this association is poorly understood. We investigated PTFV1 as a marker for functional, electrical, and structural atrial remodelling. Methods and results: Fifty‐six patients with acute myocardial infarction and 13 kidney donors as control cohort prospectively underwent cardiac magnetic resonance imaging to evaluate the association between PTFV1 and functional remodelling (atrial strain). To further investigate underlying pathomechanisms, right atrial appendage biopsies were collected from 32 patients undergoing elective coronary artery bypass grafting. PTFV1 was assessed as the product of negative P‐wave amplitude and duration in lead V1 and defined as abnormal if ≥4000 ms*μV. Activity of cardiac Ca/calmodulin‐dependent protein kinase II (CaMKII) was determined by a specific HDAC4 pull‐down assay as a surrogate for electrical remodelling. Atrial fibrosis was quantified using Masson's trichrome staining as a measure for structural remodelling. Multivariate regression analyses were performed to account for potential confounders. A total of 16/56 (29%) of patients with acute myocardial infarction, 3/13 (23%) of kidney donors, and 15/32 (47%) of patients undergoing coronary artery bypass grafting showed an abnormal PTFV1 . In patients with acute myocardial infarction, left atrial (LA) strain was significantly reduced in the subgroup with an abnormal PTFV1 (LA reservoir strain: 32.28 ± 12.86% vs. 22.75 ± 13.94%, P = 0.018; LA conduit strain: 18.87 ± 10.34% vs. 10.17 ± 8.26%, P = 0.004). Abnormal PTFV1 showed a negative correlation with LA conduit strain independent from clinical covariates (coefficient B : −7.336, 95% confidence interval −13.577 to −1.095, P = 0.022). CaMKII activity was significantly increased from (normalized to CaMKII expression) 0.87 ± 0.17 to 1.46 ± 0.15 in patients with an abnormal PTFV1 ( P = 0.047). This increase in patients with an abnormal PTFV1 was independent from clinical covariates (coefficient B : 0.542, 95% confidence interval 0.057 to 1.027, P = 0.031). Atrial fibrosis was significantly lower with 12.32 ± 1.63% in patients with an abnormal PTFV1 (vs. 20.50 ± 2.09%, P = 0.006), suggesting PTFV1 to be a marker for electrical but not structural remodelling. Conclusions: Abnormal PTFV1 is an independent predictor for impaired atrial function and for electrical but not for structural remodelling. PTFV1 may be a promising tool to evaluate patients for atrial cardiomyopathy and for risk of atrial fibrillation.